Evaluation of Organic and Inorganic Amendments on Soil Physicochemical Properties in Soybean (Glycine max L.) Cultivation - Vibhuti Singh Jhala; Priyanka Bankoti (The Bioscan, 2025)
Soil health is a fundamental determinant of crop productivity. Deterioration of its physical properties led to depletion of soil fertility which are the main constrains in food and environment security (Titirmare et al., 2023). Experimental Design used for the study was CRBD (Complete Randomize Block Design) with three replications of each treatment. Ten different treatments involved in the study were T1 Control (Recommended dose of fertilizers) T2 (50% NPK + Vermicompost), T3(50% NPK + Farm yard manure, T4 (50% NPK + Rhizobium japonicum), T5 (50% NPK + PSB (phosphate solubilizing bacteria), T6(50% NPK + Mycorrhiza, T7(50% NPK + 25% Vermicompost +25% Farm yard manure), T8(50% NPK + 25% Rhizobium japonicum + 25% PSB + 25% Mycorrhiza), T9(50% NPK + 25% Vermicompost +25% Farm yard manure + 25% Rhizobium japonicum), T10(20% Chicken manure +20% Farm yard manure + 20% Rhizobium japonicum + 20% PSB + 20% Mycorrhiza). The result indicate that the lowest bulk density (1.27 mg/m3) was observed in the T2 (50% NPK+ Vermicompost). Organic content was highest (0.38%) in treatment T2 (50% NPK+ Vermicompost and T7 (50% NPK + 25% Vermicompost +25% Farm yard manure). Result indicate that the lowest bulk density (1.27 mg/m3) was observe in T2 (50% NPK+ Vermicompost) treatment. Organic content was highest (0.38%) in treatments with T2 (50% NPK+ Vermicompost) and T7 (50% NPK+ 25% Vermicompost + 25% FYM). Lowest soil pH (7.22pH) was observed in 50% NPK+ Vermicompost and T7 (50% NPK+ 25% Vermicompost + 25% FYM). Electrical conductivity significantly decreased after soybean harvest across all the treatment, which was recorded lowest in T10 (20% Chicken manure +20% Farm yard manure + 20% Rhizobium japonicum + 20% PSB + 20% Mycorrhiza). The study showed that, using organic and inorganic in integrated form is an alternative system for the sustainable and cost-effective management of soil health without affecting environment.